THE EFFECT OF LOVE OF MONEY ON THE PERCEPTION OF TAX EVASION ETHICS WITH TRI NGA AS A MODERATING VARIABLE - Erawati, Teguh; Listyawati, Reni; Riu, Maria Guilhermina Funan Guterres (International Conference on Humanity Education and Society (ICHES), 2024)
Tax is a taxpayer contribution to the state owed by individuals or entities that are compelling based on the law, with no direct reward and used for state purposes for the continuity and prosperity of the people. In addition, taxes are also one of the largest sources of state revenue. This study aims to examine the love of money on the perception of tax evasion ethics with tri nga as a moderating variable. The data used in this study is using primary data. The population of this study were all accounting students in the 2019-2023 batch of Yogyakarta Special Region with a research sample of 50 respondents. The research analysis method is moderated linear regression which includes descriptive statistical methods, classical assumption tests, and hypothesis testing. Based on the research conducted, it proves that Love of money has a positive effect on the ethical perception of tax evasion, Tri nga can moderate Love of money on the ethical perception of tax evasion.